Effects of Socio-economic and academic factors on the performance of engineering students at the University of Moratuwa - De Silva, H.V.S.; Karunaratne, A.; Dharmarathne, H. A. S. G. (University of Colombo, 2010)
The purpose of this study is to determine the factors that influence the final academic performance of the students focusing on the student’s socio-economic background and Grade Point Average (GPA) of Mathematics modules of the first two years of engineering students at the University of Moratuwa. Univariate Analysis was initially used to identify relevant factors for this study. To obtain a model for predicting the final result of students, Ordinal Logistic Regression (Proportional Odds Model) was used. Multivariate Analysis is also used to obtain latent factors. A key finding is that the GPA of Year two Mathematics modules, Field of study and Language Problems have a significant impact on the final academic performance of the graduates. It was found that students with less language problems are more likely to obtain higher category results. Field of study , Language Problems and GPA of Year 2 Mathematics modules have highly significant effects on the final result. Possibility of getting lower to higher category results for those who do not have language problems is approximately twice that of those who have language problems while the above odds for those with Grade Point Average (GPA) of Mathematics modules greater than or equal to 3.8 is twice that of those with GPA between 3.1 and 3.7. Descriptive Analysis revealed that most of the First and Second Upper classes have been obtained by students in the Colombo district